Enhancing the prospects for palliative care at the end of life: A statewide educational demonstration project to improve advance care planning. Issue 6 (20th June 2016) - Litzelman, Debra K.; Cottingham, Ann H.; Griffin, Wilma; Inui, Thomas S.; Ivy, Steven S.
Abstract: Objective: Although patients want to participate in discussions and decisions about their end-of-life care, studies show that providers frequently fail to invite them to explore advanced care preferences or goals for living. The purpose of our demonstration project was to provide education and coaching to individuals, health providers, and organizations across the state of Indiana intended to facilitate these conversations, documenting and honoring individuals' life goals and preferences for care during the final stages of life. Method: Education and training engaged community members as well as healthcare providers to: (1) improve participant comfort and facility discussing end-of-life issues; (2) improve knowledge of healthcare choices, including palliative and hospice care; and (3) prepare all participants to explore and document personal values, life goals, and priorities as well as goals of care. Results: Between January of 2013 and June of 2015, the team educated close to 5, 000 participants. Participants' ratings of the quality and perceived usefulness of the educational events ranged from 4 to 5 (using a 5-point scale, with 5 = most effective). Participant comments were overwhelmingly favorable and indicated an intention to put the advance care planning resources, communication skills, knowledge of palliative and hospice care, and personal renewal techniques into practice. Significance of Results: Participant motivation to foster advance care planning, discussions of palliative care, and end-of-life conversations was facilitated by the reframing of these conversations as identifying goals of care and priorities for living well during an important stage of life. Successful strategies included helping providers and patients to adopt a broader meaning for "sustaining hope" (not for cure, but for engaging in highly valued activities), developing provider communication skills and comfort in initiating potentially difficult discussions, engaging a new community health workforce who will develop trusting relationships with patients in home-based services, and fostering self-awareness and self-care among palliative care providers.